Implikatur Percakapan Dalam Kostum (Komik Strip Untuk Umum) Karya Haryadi Periode Januari - Maret 2019 (Kajian Pragmatik) - Tuti; Nurul Ilmi (KOLONI, 2025)
This research aims to (1) Analyze the forms of conversational implicature and violation of maxims in the principles of cooperation according to Paul Grice's theory as a support for humor found in KOSTUM (Comic Strip for General) by Haryadhi from January 1, 2019, to March 31, 2019. This study uses a qualitative descriptive method. The object of the study is KOSTUM (Comic Strip for General). The data used consists of 17 pieces obtained using basic techniques such as reading KOSTUM (Comic Strip for General) for data collection, identifying written data, transferring the data to notes, collecting literature sources, and other source data. The theoretical framework used related to Conversational Implicature is Paul Grice's theory. The analysis results include: (1) The forms of conversational implicature consist of representative implicature 'stating' 2 data, 'showing' 2 data. Expressive implicature 'criticizing' 1 data, 'complaining' 1 data. Directive implicature 'demanding' 1 data for 'commanding', and 1 data for 'requesting'. Meanwhile, (2) Violations of the maxims in the principle of cooperation include: maxim of quantity (Maxim of Quantity) 4 data, maxim of quality (Maxim of Quality) 1 data, maxim of relevance (Maxim of Relevance) 1 data, and maxim of manner (Maxim of Manner) 3 data.